Regulating Water Concessions : Lessons from the Buenos Aires concession - Crampes, Claude; Estache, Antonio (World Bank, Washington, DC, 2012)
The Argentine government privatized the water and sewerage services in greater Buenos Aires by concession. The utility was sold as a single monopoly business, but bidders had to compete for the right to provide service at the lowest price. Contractual targets for service coverage implied significant investment over the life of the contract. As things have turned out, the assets were in worse shape than expected, and a renegotiation rule has allowed a tariff hike to pay for accelerated investment. The authors argue, however, that the pricing system is still flawed, producing incentive problems for investment.